Corruption and money laundering : a symbiotic relationship - Chaikin, David A. (Palgrave series on Asian governance., 2009)
Corruption is the biggest single obstacle to development, while money laundering is at the heart of all profit-driven crime. The failure to appreciate the intimate linkages between these two crimes has undermined international efforts to combat these global scourges. Through a policy and legal analysis, this book shows how corruption facilitates money laundering and vice versa. It demonstrates how strategies utilized to counter one type of financial crime can be adapted to fight the other. Chaikin and Sharman provide a pioneering evaluation of the current systems from multi-disciplinary perspective based on professional experience and extensive interviews.